A retrospective analysis of cardiometabolic health in a large cohort of truck drivers compared to the American working population. Issue 2 (8th November 2017) - Thiese, Matthew S.; Hanowski, Richard J.; Moffitt, Gary; Kales, Stefanos N.; Porter, Richard. J.; Ronna, Brenden; Hartenbaum, Natalie; Hegmann, Kurt T.
Abstract : Background: Truck drivers face many health challenges, including lifestyle, diet, inactivity, stressors, and social support. Methods: A repeated cross‐sectional analysis compared 88, 246 truck drivers with data from ( n  = 11 918) the National Health and Nutrition Examination Survey (NHANES). Trends over time for body mass index (BMI), high blood pressure, diabetes mellitus, heart disease, and sleep disorders were analyzed, adjusting for potential confounders. Results: Truck drivers had significantly worsening health metrics between 2005 and 2012 compared to NHANES participants. Truck drivers were significantly more likely to be obese and morbidly obese with prevalence odds ratios (POR) and 95% confidence intervals (95%CI) of 1.99 (1.87, 2.13) and 2.34 (2.16, 2.54), respectively. Measured blood pressure, self‐reported high blood pressure, diabetes mellitus, and heart disease all significantly increased. Also, sleep disorders increased among truck drivers from 2005 to 2012 (POR = 6.55, 95%CI 5.68, 7.55). Conclusion: These data suggest disproportionate increases in poor health among truck drivers from 2005 to 2012.